Magnetic resonance imaging changes in multifidus and psoas muscles in patients with lumbar spinal stenosis - Çavuş, Gökhan; Çavuş, Yeliz (The European Research Journal, 2021)
Objectives: The aim of this study is to evaluate the relationship between the spinal canal cross-sectional area (SCCSA) at the stenosis level, the cross-sectional areas of the multifidus (MF) muscle at the L3-S1 levels, and the cross-sectional areas of the psoas muscle (PSCSA) at the L3 level in patients with nerve compression due to lumbar spinal stenosis. Methods: A total of 280 patients were included in the study, 140 in the control group and 140 with lumbar spinal stenosis that had been detected with magnetic resonance imaging (MRI). The patients' ages, gender, SCCSA at the level of stenosis, PSCSA at L3 level, MFCSA at L3-S1 levels, and degrees of atrophy caused by multifidus muscle fatty degeneration were evaluated and compared with the control group whether the comparison was statistically significant or not. Results: PSCSA values at the L3 level and MFCSA at the L3-4 level (r=0.555, p < 0.01), MFCSA at the L4-L5 level (r=0.559, p < 0.01), and MFCSA at the L5-S1 level (r=0.429, p < 0.01) were found to have a statistically significant positive correlation. In addition, MFCSA at the L3-4 level (p < 0.001), MFCSA at the L4-5 level (p < 0.001), MFCSA at the L5-S1 level (p < 0.001),the L3-L4 SCCSA (p < 0.001), and the L4-L5 SCCSA (p < 0.001) mean values were found to be statistically significantly lower than the mean of the cases in the control group. Conclusions: Compared to the control group, a significant correlation was found with a decrease in the CSA of the multifidus muscle and the presence of fatty degeneration of the multifidus muscle in patients with spinal stenosis. However, in the CSA of the psoas muscle at the L3 level, it was found that there was no correlation between patients with spinal stenosis and the control group.